Resilient or merely different? Reading the 2026 correction of Indonesia’s Islamic capital market - Dimvy Rusefani Asetya (Journal of Islamic Economic Insights, 2026)
In the first half of 2026, Indonesia’s Islamic capital market produced a striking divergence. According to the Financial Services Authority (OJK), the Indonesia Sharia Stock Index (ISSI) fell by more than 36% between May and June 2026 and Shariah-compliant market capitalisation contracted sharply, even as outstanding corporate sukuk grew by more than 15% year-to-date and sovereign sukuk held broadly stable (OJK, 2026). This commentary reads that divergence as a natural experiment on a claim frequently made for Islamic finance—that it is inherently more stable and resilient than its conventional counterpart. Drawing on Scopus- and Web of Science–indexed scholarship, the article argues that the resilience of sukuk relative to Shariah-screened equities reflects instrument structure rather than any distinctively “Islamic” immunity to risk; that Shariah screening does not insulate equity investors from systematic shocks; and that the market’s deeper vulnerability lies in a banking market share stalled near 7% and a shallow investor base. It contends that durable resilience must be built through substantive risk-sharing and Maqasid-oriented market depth rather than through compliance labelling, and it offers policy directions for Indonesia’s regulators and market builders.